Leadership Practices On Employee Performance With Motivation And Job Satisfaction - Faturohman, Deden; Subhan (Journal of Management, 2024)
The purpose of this study is to look at the impact of leadership techniques on employee performance, using motivation and job satisfaction as mediating variables. This study used a quantitative method and included 100 individuals from diverse industries as respondents. Leadership behaviors have a positive and significant impact on employee performance (β = 0.513, p < 0.001), with a R² value of 0.427. The regression model can explain approximately 42.7% of employee performance variability. Job satisfaction had no significant effect on employee performance (β = 0.179, p = 0.110), suggesting it may not be a relevant factor in this model. This study demonstrates that good leadership techniques contribute significantly to better employee performance, although work satisfaction, while important, has no meaningful impact in this model. These findings encourage managers and organizational leaders to prioritize strengthening leadership practices as a critical strategy for enhancing employee performance. This study also emphasizes the need for additional research to investigate other factors that may affect employee performance in more depth.